Experimental Study of the Influence of the Concentration of Organic Water-Coal Fuel Components on the Integral Ignition Characteristics; Journal of Engineering Physics and Thermophysics; Vol. 90, iss. 1 - Vershinina K. Yu. Kseniya Yurievna (2017, 2017)
Title screen